Theatrical locations in digital role-playing games as a starting point for the reflection on the remediation of theater in computer games - Kłeczek, Jakub (Replay. The Polish Journal of Game Studies, 2014)
Digital games and theatre seem to have similar identity. This may be observed in similar art techniques used in both media. The aim of this paper is to demonstrate how theatre as a medium is represented in digital games. Analysis of selected games using theatrological methods shows the ludological problem of immersion in a new and interesting way. The subject of study is theatrical video game locations in Pathologic, The Path, Final Fantasy IX and The Elder Scrolls III: Morrowind. According to the author, analysing such locations is a good starting point for the discussion about the remediation of theatre and digital games.